Comportamiento de la repoblación natural de Pinus arizonica Engelm. bajo diferentes coberturas - Chacón Sotelo, Juan Manuel; Velázquez Martínez, Alejandro; Musálem, Miguel Angel (Instituto de Ecología, A.C., 2016)
The proper management of forest stands requieres knowledge about number, arrangement, and characteristics of seedtrees after the application of a reproduction method. In order to determine the number of seed-trees best suited in the seed-trees repopulation method in a Pinus arizonica Engelm. natural stand in Chihuahua state, the effect of five degrees of canopy closure (64.5, 119.5, 204.0, 233.0 y 345.0 m2 ha-1) on seed germination, and survival and growth of seedlings was evaluated at 6, 12 , 18 and 34 months after the application of final cut. Seed germination of the species was better in canopies of 64.50 m2 ha-1; however, in this condition high mortality occurred, specially inmediately after seed germination. Greater seedling growth was observed between seedling ages 6 and 12 months under wide canopy openings.